A review of herb-induced liver injury in mainland china - Yang, Yan; Ge, Fei-Lin; Tang, Jin-Fa; Qin, Shuang-Lin; Zeng, Rui; Yao, Meng-Lin; Xiao, Xiao-He; Bai, Zhao-Fang; Tang, Cheng-Lin (Frontiers in Pharmacology, 2022)
Traditional medicines have greatly contributed to the health of people around the world. However, in recent years, the frequent occurrence of herb-induced liver injury (HILI) have raised public concerns about the safety of herbs. HILI not only has a serious impact on public health, increasing its medical burden, but also expends medical resources. However, the pharmacoepidemiology and risk factors of HILI are still unclear due to the complexity of herbs (medication theory, drug composition, dual properties of drug and food , etc. ). China, as the country with the most extensive use of herbs and exists the most cases of HILI in the world, the safety profile of herb (especially HILI) has affected the use of herbs internationally as well. Therefore, this study centers on the epidemic situation of HILI in China as a window to review its characteristics, while focusing on three main aspects of patients, drugs, and unreasonable prescription to explore the potential risk factors. Our aim is to provide a reference for HILI pharmacovigilance and risk prevention and control, while contributing a piece of Chinese wisdom to the realization of World Health Organization's "Medication Without Harm" global safe medication strategic goal.